Atomic force microscopy and other scanning probe microscopy methods to study nanoscale domains in model lipid membranes. Issue 1 (31st December 2023) - Robinson, Morgan; Filice, Carina T.; McRae, Danielle M.; Leonenko, Zoya
ABSTRACT: The cell membrane is a fundamental biological structure, which is only 6–10 nm thick. It is composed of hundreds of lipid types, which form small and dynamic lipid domains or rafts. These rafts are thought to be a major aspect of cell organization, to provide support for various transmembrane proteins and are central to the communication of cells with their environs. Understanding the functions of lipid rafts presents an exciting opportunity to understand the molecular mechanisms of biologically important processes, as well as to uncover fundamental molecular mechanisms of membrane-associated diseases. Due to the high complexity of cell membranes, model membranes composed of synthetic lipids have been developed and are widely used to mimic biomembranes in an effort to study the structure and dynamics of lipid domains and their role in cell function. Atomic force microscopy (AFM), Kelvin probe force microscopy (KPFM) and atomic force spectroscopy (AFS) significantly advanced the study of nanodomains in model lipid membranes and monolayers. We review applications of these methods to the study of model membranes, which are widely used to mimic eukaryotic and bacterial cells, as well as neuronal cellular membranes in Alzheimer's disease (AD). Graphical Abstract: uf0001